Women's Leadership Research in Higher Education Institutions (HEIs): A Bibliometric Study - Widyatami, Kania -; Sobandi, A. - (Manajemen dan Bisnis, 2025)
Gender disparity in leadership positions has been a topic of discussion for a considerable amount of time, including in the context of Higher Education Institutions (HEIs). This study applied bibliometric analysis to reveal how the field evolved. The data was retrieved from the Scopus database from 1952–2023 and processed using R software’s “bibliometrix” package and the Publish and Perish applications. A range of techniques comprising performance analysis and science mapping through co-citation analysis, bibliographic coupling, and co-word analysis were performed to uncover the intellectual, knowledge, and conceptual structures that give insights regarding the trends as well as the past, present, and future of the field.